Effect of percentage of graphene oxide on phase transition of water induced shape memory behavior of PVA-go-PEG hydrogel. (12th September 2018) - Wu, Guanzheng; Li, Siming; He, Wentao; Xiao, Xueliang
Abstract: Since supramechanical hydrogel was reported, hydrogel has been becoming a popular material to construct specialty features or functions. In this paper, a functional hydrogel made of poly (vinyl alcohol)/graphene-oxide/polyethylene-glycol (PVA-go-PEG) was investigated for the percentage effect of graphene-oxide (GO) on the phase transition of water induced shape memory ability. Experimentally, the hydrogel showed high shape fixed ability at below −5 °C and high shape recovered ratio at above 5 °C for GO content of 0.6%, 0.9% and 1.2%. The temperature range from −5 to 5 °C gives rise to a fixation and recovery dynamics of hydrogel for each GO content, thus the state of aqueous molecules inside hydrogel dominates the dynamic behavior. Characterizations from XRD, FTIR and NMR indicated that the crystalline phase in polymers and the generated hydrogen bonds between GO nanoparticles and macromolecules play key role of netpoints for maintaining hydrogel shape intact. DSC and XRD measured spectra revealed that the phase transition of aqueous molecules in the hydrogel act as switch in the shape memory program. A model for such shape memory mechanism was proposed to explain the effect of GO content on the phase transition of water induced shape memory behavior for the prepared hydrogel. This study inspires to explore high strength and adaptability of hydrogels in application areas of temperature conversion conditions.